PENGARUH MODEL PEMBELAJARAN VCT TERHADAP SIKAP NASIONALISME SISWA SMAN 9 PADANG - Diani Putri; Zafri Zafri (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
Seeing the learning process is a process of communication that school is a world that is bound by its own small communication. The success of an educational process is not only measured from the cognitive aspect of students, but no less important in terms of affective and psychomotor aspects are also determining factors for the success of an educational process. Therefore, in addition to family and the environment, when children enter the world of education, teachers also play an important role in shaping the attitudes of their students, especially attitudes related to students' sense of love for their homeland, namely student nationalism. By using the VCT model, educators are forced to slowly start instilling the values of nationalism. Through a learning model that is able to create a society that has an attitude of nationalism and patriotism to increase the behavior of nationalism of students so that they have character and temperament.